Implementasi Augmented Reality Pada Aplikasi HOPE Berbasis Android - Ihzany Vilia Devi; Suroso Suroso; Nasron Nasron (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
In studying telecommunications, students are required to master telecommunications equipment that is often used in laboratories. The high cost of telecommunications equipment causes students to take turns in observing and studying telecommunications equipment. If students are not careful in using telecommunications equipment owned by the laboratory, it is likely that the equipment will be damaged quickly, causing the learning process to be disrupted. Then we need an interactive application that can provide visual and auditory learning based on Android that can be accessed anytime and anywhere. So in this study, a HOPE application which means "hope" is designed using an android-based augmented reality. The research method used is the Marker Based Tracking method that uses three main axes namely X, Y, and Z with the help of coordinates (0, 0, 0) and also virtual in 3 dimensions. Three-dimensional objects will be marked with three main axes namely X, Y, and Z to appear virtual objects. The results of this research are to increase knowledge in the field of telecommunications, be able to increase the interest of new students in telecommunications engineering study programs, facilitate lecturers in teaching, and facilitate students to understand telecommunications equipment independently.